LACK OF TRANSPARENCY IN THE FORMATION OF THE TNI BILL ON THE PRINCIPLES OF THE RULE OF LAW AND CIVIL SUPREMACY IN INDONESIA - Annelies Larasati Gufron; Muhammad Rizqi Ramadhan; Sabrina Syarif; Dwi Nurfauziah Ahmad (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This research aims to critically examine and analyze the lack of transparency in the process of forming the Indonesian National Army Bill (RUU TNI) in 2025 and its implications for the principles of the state of law and civil supremacy in Indonesia. Using normative juridical methods with a qualitative approach and literature study, this study found that the formation of the TNI Bill was carried out behind closed doors, without adequate public involvement, and not accompanied by published academic manuscripts. The main findings include violations of the principle of legislative transparency, indications of the expansion of the TNI's authority into the civilian realm without strong civilian control, and inconsistency with the participatory principle in constitutional law. This undemocratic legislative process shows a regression in the system of checks and balances and threatens civil supremacy as the main pillar of a democratic state. This research suggests the need to reform the legislative process to ensure community involvement and maintain the integrity and constitutional legitimacy of the resulting legal products.